Plant Communities Associated with Sal (Shorea robusta) Regeneration in Dehra Dun Valley - Khan, M. A. Waheed; Gupta, A. C. (Indian Forester, 1960)
A phytosociological study of sal (Shorea robusta) regeneration was made in B. 3-High Level Alluvium sal forests of the Dehra Dun valley. The occurrence and condition of sal regeneration was precisely determined with regard to forest stratification and spatial distribution of species. The ecological methods adopted were modified belt transects with thorough cartography of vegetation, involving accurate charting and profile representation. Both favourable and unfavourable communities with regard to sal regeneration have been distinguished and the role of competition is stressed. Favourable associates apparently do not compete with sal seedlings for light, moisture and nutrients, and may. on the contrary produce a congenial and cool atmosphere for rapid growth. This study, therefore, is suggestive of the fact that in practice it is advisable to deal drastically with the unfavourable type of shrubby growth and ground flora, along with adequate canopy manipulation, for obtaining and establishing sal regeneration.